Formation and sustenance mechanism of bacterial diversity in nutrient-deficient environment of indoor stadium - Lei Sun; Xiao Wen; Lei Li; Min Li; Xiaodong Xing; Zhiyong Zhang; Chen Dong (Scientific Reports)
Abstract Bacterial diversity has been found in indoor stadiums which can be considered as a specific nutrient-deficient environment (NDE), it remains a mystery and opens to new ideas why the bacterial diversity can be formed and maintained in NDE of indoor stadiums, since it is obvious to violate the famous competitive exclusion principle (CEP) in ecology. In the article, five most common genera, Pseudomonas, Acinetobacter, Exiguobacterium, Sphingobacterium, Chryseobacterium in indoor stadiums were selected and periodically sampled to supervise the dynamic characteristics of bacterial community. Based on quorum sensing (QS) and non-monotonic interspecific interaction (NMII) in combination with microbial ecology, clustering analysis and experimental observation, a new hypothesis was put forward to elucidate QS and NMII of substrate location information (SLI) mechanism driving bacterial community succession with high diversity in NDE of indoor stadium. A valid cellular automation (CA) model was derived from assumptions directly, and the CA simulation sufficiently proved that QS and NMII of SLI can effectively weaken interspecific competition to drive the spatiotemporal succession of bacterial community in NDE of indoor stadium towards a climax community with high richness and evenness, namely bacterial diversity. The succession mechanism confirmed by CA simulation can set up a theoretical framework for comprehensive apprehension about ecological effect of QS with NMII of SLI sharing on formation and sustenance of bacterial diversity in NDE of indoor stadium.